Association of overweight and obesity with breast cancer in India - P Singh; Umesh Kapil; N K Shukla; SVS Deo; S N Dwivedi (Wolters Kluwer Medknow Publications, 2011)
Background : In women, cancer of the breast is one of the most common incident cancer and cause of death from cancer. Anthropometric factors of weight, height, and body mass index (BMI) have been associated with breast cancer risk. Objectives : To study the association of overweight and obesity with breast cancer in India. Materials and Methods: A hospital-based matched case-control study was conducted. Three hundred and twenty newly diagnosed breast cancer patients and three hundred and twenty normal healthy individuals constituted the study population. The subjects in the control group were matched individually with the patients for their age ±2 years and socioeconomic status. Anthropometric measurements of weight and height were recorded utilizing the standard equipments and methodology. The paired 't' test and univariate logistic regression analysis were carried out. Results: It was observed that the patients had a statistically higher mean weight, body mass index, and mid upper arm circumference as compared to the controls. It was observed that the risk of breast cancer increased with increasing levels of BMI. Overweight and obese women had Odd's redio of 1.06 and 2.27, respectively, as compared to women with normal weight. Conclusions: The results of the present study revealed a strong association of overweight and obesity with breast cancer in the Indian population.